(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2007)
In the ores of Thukhmanuk gold-polimetallic deposit gold and silver is presented in native and isomorphous form. The content of free gold is 30%, two times less silver (13–15%). In the monominerals of sfalerite, chalkopyrite, pyrit, galenit the contents of Au and Ag vary within the limits of 14.2–21.3 g/t and 44.7–82.4 g/t correspondingly.